Mapping the Evolution of Research Themes on ChatGPT Integration in Education: Thematic and Novelty Keywords - Nabilah, Nabilah; Zafrullah, Zafrullah; Nakamo, Sosteness Jerome; Mwakapemba, Morris Leonard (Penerbit Hellow Pustaka, 2025)
Abstract. This study aims to examine the evolution and novelty of keywords in the field of ChatGPT in Education using a bibliometric approach. By applying a predefined set of keywords, the researchers identified 310 publications from the Scopus database, which were then analyzed using R Program. The analysis focused on main information, publication trends, keyword evolution over time, and keywords novelty. This analysis concludes that research on ChatGPT in the field of education within the Scopus database began in 2022 and continued through 2025, with the highest surge in publications occurring in 2024, reaching 171 documents. Overall, the findings reveal that the topic of ChatGPT in Education has experienced significant growth, with several core keywords such as